Guillermo de Torre en Chapel Hill - Antoni Martí Monterde (Mélanges de la Casa de Velázquez, 2016)
Guillermo de Torre is a very well-known figure for the part that he played in the Ultraist movement, and as the author of Literaturas Europeas de Vanguardia (1925). However, his reputation as a literary critic does not generally include his involvement in Comparative Literature, which actually prompted him to take part in the second congress of the International Comparative Literature Association (AILC/ICLA), held in 1958 at Chapel Hill in the USA. The purpose of this article is to present Guillermo de Torre’s career as a comparativist—obviously not without qualifications—and to recall his lecture at that congress as a proposal—at once intelligent and problematical—to look comparatively at the relations between the various different Hispanic literatures.